Cost of Power Generation with Different Fuels at Different Locations - Planning Commission (Planning Commission, 1998)
Planning Commission had earlier in Aug. 1995 carried out an analysis to work out comparative cost of Power Generation using various fuels at different locations considering cost of transportation for these fuels from supply points (at producing fields and port locations for imported fuels) to the power plants. Analysis was carried out based on the imported as well as domestic fuels on financial basis for having a broad idea on choice of optimal fuel for power generation at different regional locations.
An Approach Towards Fuel Policy For Power Generation
Power and Energy Division Planning Commission Government of India New Delhi